Too Much of a Good Thing? The Impact of Initial Prescription Size in Post-Cesarean-Delivery Pain Management [A265]. (May 2022) - Goodrich, Robyn N.; Nunziato James, Jaclyn D.; Hagerdorn, Meghan K.; Spivey, Cara N.; Tegge, Allison; Locklear, Tonja M.
Abstract : INTRODUCTION: Abuse of prescription opioids has reached epidemic proportions, and research demonstrates that prescription opioids used in post-cesarean-delivery pain management contribute significantly to this epidemic. Research in other surgical specialties demonstrated that patients consume about half of their initial prescription dose; however, this theory has yet to be applied to the field of obstetrics and gynecology. The objective of this research is to determine if initial prescription size influences patient consumption of opioids for post-cesarean-delivery pain management. METHODS: This randomized controlled trial involves 170 opioid-naive women ages 19–40 years undergoing scheduled cesarean deliveries at Carilion Roanoke Memorial Hospital. Patients were randomized to receive either 10 or 20 tabs of oxycodone 5 mg as an initial postoperative prescription in a double-blinded, parallel trial design. Outcome metrics regarding opioid consumption patterns and pain control were collected at three different time points postoperatively: 2–3 days, 10–14 days, and 6 weeks. RESULTS: Preliminary data (n=62) demonstrates that an average of 5 (±3.73) opioid tablets were consumed postoperatively in the 10-tablet group, compared to 8.4 (±8.87) tablets in the 20-tablet group ( P =.05). Moreover, no participant requested additional refills of opioids. CONCLUSION: We observed that the average number of opioids consumed for adequate postoperative pain management was about half of the initial prescription size in both groups. Preliminary data supports the idea that initial prescription size influences patient opioid consumption. This study has direct implications to support a standard reduction of opioid prescriptions for post-cesarean pain management and the potential to directly impact millions of women every year.